Decreasing Harmonics via Three Phase Parallel Active Power Filter Using Online Adaptive Harmonic Injection Algorithm - Karaman, Omer Ali; Erken, Faruk; Cebeci, Mehmet (Univ Osijek, Tech Fac, 2018)
Three-Phase Parallel Active Power Filter (PAPF) control mechanism via a novel Adaptive Harmonic Injection (AHI) algorithm is proposed in order to filter out harmonics generated by non-linear loads and carry out reactive power compensation. The presented PAPF mechanism is composed of two stages. Before is the extraction of reference current to determine currents with harmonics. Once the reference current is determined, according to the reference current, appropriate current harmonics are injected by triggering of the inverter switches. The proper amplitude and phase values of the harmonics that will be injected are estimated online at any instant by the AHI algorithm. In this study, the sine and the cosine of the phase angle for any harmonic order is weighted by the values estimated via the AHI algorithm, thus obtaining harmonic orders at the desired amplitude and phase. Simulations are performed using various non-linear loads in order to validate the proposed method.
Keywords: adaptive algorithms; Parallel Active Power Filter; power quality; power system harmonics; total harmonic distortion